2020
DOI: 10.1002/jso.26349
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for predicting overall and recurrence‐free survival after trimodality therapy for esophageal adenocarcinoma

Abstract: Background Locally advanced esophageal carcinoma is treated with neoadjuvant chemoradiation and esophagectomy. Patients may still experience recurrence and death despite undergoing potentially curative trimodality therapy. This study describes predictive nomograms for recurrence‐free (RFS) and overall survival (OS) after the completion of trimodality therapy. Methods A total of 215 patients with esophageal adenocarcinoma underwent trimodality therapy from September 2010 to April 2018. Multivariate Cox proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Based on the latest AJCC staging system (the 8th edition), pathological grade is not a staging factor for patients receiving neoadjuvant therapy. However, we found that the pathological grade was an independent risk factor for OS among patients receiving nCRT plus surgery, which was consistent with that of other reports ( 9 , 10 ). He et al noted that EC patients with poorly differentiated tumors respond better to nCRT than those with well-differentiated or moderately differentiated tumors; however, they have extremely poor long-term survival rates ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…Based on the latest AJCC staging system (the 8th edition), pathological grade is not a staging factor for patients receiving neoadjuvant therapy. However, we found that the pathological grade was an independent risk factor for OS among patients receiving nCRT plus surgery, which was consistent with that of other reports ( 9 , 10 ). He et al noted that EC patients with poorly differentiated tumors respond better to nCRT than those with well-differentiated or moderately differentiated tumors; however, they have extremely poor long-term survival rates ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we constructed well-calibrated prognostic nomograms to predict OS and CSS in patients with EAC. Consisting with prior research studies, predictive parameters including age, marital status, insurance, tumor differentiation, and TNM stage were associated with OS and CSS [ 12 , 22 25 ]. Patients over 60 years of age, from a family relatively lack of care and support, with the poor tumor differentiation and in advanced stage had the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, neoadjuvant chemoradiation followed by esophagectomy (trimodality therapy) is the standard treatment of locally advanced esophageal carcinoma [ 11 ], but a significant proportion of patients relapse and die after treatment. Despite several prognostic evaluations assessed trimodality therapy or pharmaceuticals treatments (proton pump inhibitors (PPIs), statins, nonsteroidal anti-inflammatory drugs (NSAIDs) and metformin) impacting the outcomes [ 12 , 13 ], an ideal prognostic model with the value of accuracy and applicability for EAC needs to be set.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 69 studies were used to analyze the distribution of PNI in different pathological types of EC, including 24 studies on EC (ESCC, EAC, and other types including esophageal small cell undifferentiated carcinoma and esophagus carcinosarcoma) ( 6 – 8 , 10 30 ), 32 studies on ESCC ( 9 , 31 61 ), and 13 studies on EAC ( 62 74 ). The detailed information is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%